2021
DOI: 10.1057/s41289-021-00151-z
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 as an “invisible other” and socio-spatial distancing within a one-metre individual bubble

Abstract: Inspired by the social representation theory, the article embraces many aspects of the way in which the space dimension in social distancing has become a central measure for both one’s own and others’ health protection during the Covid-19 pandemic, evoking symbolic dimensions related to the social representations of “others” that are emotionally driven by fear or mirror the vulnerable self, activating the othering–otherness process. This invisible (sometimes stigmatized) “other”—never previously known—has in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 46 publications
3
53
0
Order By: Relevance
“…As recent studies suggested that the COVID-19 pandemic posed a particular contamination threat, given the lack of visible symptoms in many cases (de Rosa & Mannarini, 2021) this further supports our results on passive aggression, rather than active aggression, and the social representation of "others" as a representation of the virus itself.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As recent studies suggested that the COVID-19 pandemic posed a particular contamination threat, given the lack of visible symptoms in many cases (de Rosa & Mannarini, 2021) this further supports our results on passive aggression, rather than active aggression, and the social representation of "others" as a representation of the virus itself.…”
Section: Discussionsupporting
confidence: 90%
“…As the virus cannot be recognized through racial elements, nor through visible symptomsgiven that some of the persons infected are asymptomaticall these elements would lead to a different kind of 'otherness', recently named "invisible other", manifested among others through objectification (i.e. transforming the abstract into an image, materializing the 'invisible enemy') (de Rosa & Mannarini, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…With reference to this, they talked about a "bubble feeling", an expression that recalls what Hall [42] defined as the proximity space around individuals not accessible at will by everyone. Thus, this expression condenses the need to keep distance from others to avoid contagion and to comply with the mandatory measures issued by local and National Institutions and health authorities, but it also expresses the stemming experiences of isolation, loneliness, and fear generated by these COVID-19-related measures [43,44].…”
Section: Redefinition Of Relationshipsmentioning
confidence: 99%
“…Disaster research shows that the awareness of being part of a "community of fate" and the emergence of shared identities are crucial for collective and proactive responses (Drury et al, 2019). de Rosa and Mannarini (2021) argue that in a pandemic situation, only if social embeddedness and a sense of connectedness is maintained can communities adopt social norms and behaviours which are functional in the containment of the outbreak and face the collective emergency. This argument is supported also by recent studies (Bargain & Aminjonov, 2020;Borgonovi and Andrieu, 2020) highlighting how communities with high levels of social capital socially distanced and reduced mobility during the COVID-19 pandemic more than communities with low levels of social capital.…”
Section: Introductionmentioning
confidence: 99%